Implementasi Asesmen Awal Di Pendidikan Anak Usia Dini Al-Islam Riyadhul Irfan Kadungora Garut - Aliyah, Siti; Nuraeni, Neng Dewi; Huda, Nova Nurul (LP2M STAI Al-Musaddadiyah Garut, 2025)
In this study, the background is that teachers have difficulty designing and implementing assessments relevant to the curriculum and learning objectives. This limitation is reflected in the lack of variety and assessment methods used and the use of written tests as the sole diagnostic assessment tool. Teachers encountered difficulties in interpreting assessment results, which hindered their ability to identify students' individual needs and adapt appropriate teaching approaches. The purpose of this study is to describe the implementation of initial assessment and the obstacles and challenges in implementing initial assessment at PAUD Al-Islam Riyadhul Irfan. As for the type of research used, it is descriptive qualitative research that describes the events encountered. The data collection methods used were interviews, observation, and documentation. The data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results of the research at PAUD Al-Islam Riyadhul Irfan Kadungora Garut show that cognitive initial assessments are always carried out at the beginning of each theme by creating teaching modules that are adapted to the concept map formulated with the children through e-book exposure activities or watching videos related to the learning topic using an Android TV. Meanwhile, non-cognitive initial assessments are always conducted at the beginning of each new school year by holding Zoom meetings or workshops to participate in the socialization of filling out the non-cognitive assessment instrument form prepared by a psychologist. Keywords: Early Childhood, Formative Assessment, Initial Assessment